Development of a Soccer Goalkeeper Reaction Speed Training Tool in Deli Serdang Regency - Affan Kudri Sagala; Indra Darma Sitepu (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2022)
This study aims to develop a soccer goalkeeper reaction speed training tool. The form of the tool that has been made has been validated by 3 experts, namely 1 football coach, 1 sports expert and 1 tool expert. The validation results show that the percentage for expert trainers is 94%, for sports experts 96% and for alta experts 95%. The research method used for this research is the Research and Development (R&D) method. The results of the small group trial involving 3 experts showed that the soccer goalkeeper's reaction speed tool met the eligibility criteria and to be continued into the large group trial with the average percentage value of 95%. The results of a large group trial involving 6 experts showed that the soccer goalkeeper's reaction speed tool met the appropriate criteria with a percentage of 95%. It can be concluded that this tool can help practice reaction speed for soccer goalkeepers.